Conceptions of Privacy and the Non-disclosure of Same-Sex Behaviour Among Behaviourally-Bisexual Men in Heterosexual Relationships - Schrimshaw, Eric W. (2014)
Little attention has been paid to why some behaviourally-bisexual men (i.e., men who have sex with both men and women) choose not to disclose their same-sex behaviour. Using Communication Privacy Management theory (Petronio 2002), we report on the ways these men conceptualise their same-sex behaviour as private and thus feel justified in not disclosing it to family, friends, and female partners. In-depth interviews were conducted with an ethnically diverse sample of 203 non-disclosing behaviourally-bisexual men in New York City. The men offered a number of privacy rules to justify their non-disclosure, including: 1) their same-sex behaviours were their own business and nobody else’s; 2) others had no reason to know; 3) the topic of sexual behaviour was too personal; 4) they were private people in general; and 5) it was inappropriate to discuss same-sex behaviour in many contexts. Some privacy rules were used more often to justify non-disclosure to friends and family than to female partners. These findings provide insights into the reasons for non-disclosure among behaviourally-bisexual men, offer support for and extend CPM theory for the management of sexual information, and offer insights into the importance of privacy for the design and delivery of health promotion services for this population.